DEVELOPING ISLAMIC WAQF BANK AS A MECHANISM FOR FINANCIAL SYSTEM STABILITY - Ab. Aziz, Muhammad Ridhwan (Bank Indonesia, 2017)
The establishment of Islamic banking institution all over the world is often related to the proclivity of muslims to live all aspects of their lives in accordance with the teachings of Islam. Islamic bank is one of the components in Islamic financial sector that plays very vital role to generate the growth of economics among muslim society. Indeed, Islamic bank was more robust to the financial crisis compared to the conventional banking institution. Cash waqf is a trust fund established with money to provide services to mankind in the name of Allah. The gifted capital then will be spent for all sorts of pious and social purposes inclusive for the financing and investment objectives. It is recognized that there is limited study in the area of cash waqf especially in the development of Islamic waqf bank (IWB). The main objective of this article is to analyze the possibility and obstacles in developing IWB in the mainstream Islamic financial institutions. The methodo-logy of research in this article is through a qualitative research based on interview with relevant officers in the Islamic banking, waqf, and academic sectors. The general finding in this article shows that IWB can apply cash waqf structure, whereby the cash waqf fund must be converted into fixed assets such as land and buildings. The rental income from the fixed assets and investments then can be channelled to waqf beneficiaries such as funding students’ education, health assistance, giving financing to the entrepreneur, and enhancing muslim economy in various fields. Nevertheless, a proper mechanism of IWB must be developed in order to avoid any obstacles in terms of capital requirement, risky investment, limited number of experts in the field of Islamic bank and waqf as well as legal and regulation requirement.